The Effect of Training, Compensation and Work Discipline on Employee Achievement - Bunga Hidayati; Sukaris Sukaris; Alkusani Alkusani; Heru Baskoro; Ahmad Qoni Dewantoro (Universitas Muhammadiyah Gresik, 2023)
This study aims to examine the effect of training, compensation and work discipline on work performance. Information obtained from the results of this study can be used as input for further researchers and companies. The population used in the study amounted to 99 people, using a total sampling method with a sample of 89 people. The research data is primary and secondary data, ,primary data obtained from questionnaires given to respondents and secondary data obtained from companies. The analytical model used in this study is a multiple linear regression analysis model. To find out the significance of the independent variable partially to the dependent variable used the t test technique. Meanwhile, to determine the effect of the independent variables as a whole on the dependent variable, the F test was used. The results showed that partially the training variable had an influence on the Work Performance variable, compensation had an effect on work performance, whilethe discipline variable had no positive effect on work performance variables. Overall the variables tested are able to explain changes in employee performance.